Seni Debus, Pancasila, dan Media Pendidikan Karakter Religius Siswa Sekolah Dasar - Putra, Yuda Ganda; Muyidin, Asep; Jamludin , Ujang; Leksono, Suroso Mukti (JOM, 2024)
This research aims to analyze the implementation of religious character education based on Pancasila in elementary school students through the art of Debus. A qualitative approach with descriptive analysis was employed. The research was conducted at an elementary school in Serang Regency and at one of the Lungguh Pangayom Pencak Silat Paguron located in Serang Regency. The findings indicate that Debus art has not been introduced philosophically to elementary school students in Serang Regency. However, based on interviews and observations, it can be concluded that the philosophical values embedded in Debus art, if well-implemented and structured within basic education institutions, can enhance religious values based on Pancasila in elementary school students. To optimize religious character education based on Pancasila, the government could integrate Debus art as local content in the elementary school curriculum.